Channel zero. Season three, Butcher's block [videorecording (DVD)]. - Pniowsky, Abigail; Lehmann, Keenan; Hauer, Rutger, 1944-2019-; Forsyth, Amy, 1995- (Universal, 2018)
Follows Alice Woods and her schizophrenic sister Zoe who have moved to a small town to start over. On the outskirts of town lies Butcher's Block, a hellish neighborhood where junkies roam and lawlessness abounds. The sisters encounter Joseph Peach and his family, who offer them a place with promise of a world without worry and without illness. The sisters soon find that the cost of living the good life comes at an unimaginable price.